GPS‐tracking reveals non‐breeding locations and apparent molt migration of a Black‐headed Grosbeak. Issue 2 (6th April 2016) - Siegel, Rodney B.; Taylor, Ron; Saracco, James F.; Helton, Lauren; Stock, Sarah
ABSTRACT: Black‐headed Grosbeaks ( Pheucticus melanocephalus ) have been observed to undergo prebasic molt during fall in the North American Monsoon region of the southwestern United States and northwestern Mexico, but it is unknown whether molt migration is pervasive across populations of the species. During the 2014 breeding season, we GPS‐tagged (where GPS is global positioning system) nine adult Black‐headed Grosbeaks in Yosemite National Park with archival GPS tags to determine specific locations where grosbeaks breeding in Yosemite spent portions of the non‐breeding season, and to assess whether those locations were consistent with molt migration. On 2 June 2015, one of these birds, a male GPS‐tagged on 19 June 2014, was recaptured with its GPS unit still attached. Data downloaded from the unit revealed that, by 20 August 2014, the bird had moved 1300 km from Yosemite National Park to Sonora, Mexico, where it remained until at least 15 October 2014. By 24 November 2014, the grosbeak had moved >1300 m from Sonora to the Michoacán‐Jalisco border region, where it remained until the last GPS‐determined location was obtained on 24 March 2015. The seasonal timing of these movements and the length of stay in Sonora are consistent with the expected behavior of a molt‐migrating bird. Remote‐sensed enhanced vegetation index (EVI) data indicated that the grosbeak arrived in the monsoon region near the area's annual peak in EVI, and then, as the index was declining sharply, departed for the Michoacán‐Jalisco region, where the index also declined during the same period, but substantially less so than in Sonora. Climate change in the coming decades is expected to delay the annual onset of the monsoon while also accelerating the initiation of arid, summer‐like conditions throughout much of western North America, possibly yielding a temporal mismatch between fall migration and the monsoon‐driven conditions that may be critical for molt‐migrating birds.